Correlation in Chronic Rhino sinusitis on the basis of Endoscopic and Radiology - Abdulla, Mutasim Ahmed; Alseed, Elsafi Ahmed (Asian Journal of Medical Radiological Research, 2016)
Background: There are four pairs of paranasal sinuses. These are frontal, sphenoidal, ethmoidal, and maxillary sinuses. Infection of these sinuses is one of the most common causes of patient’s visit to the otorhinolaryngologist. Method: Thirty patients each of chronic rhino-sinusitis group were included in this case. Those with recurrence of symptoms of chronic rhinosinusitis after surgical management (revision cases) were included in this study. Results: In the present study 30 cases of rhino sinusitis were included. From the 15 patient 60% were male and 40% were female. Symptoms which Commonly present in the patients in this study were nasal obstruction (93.4%) & nasal discharge (53.4%). Sneezing (40%) and headache (33.4%). Conclusion: The study conclude that nasal endoscopy was more specific in detecting osteomeatal anatomic variants whereas CT scan is more sensitive for parameters.